Pengaruh Literasi Keuangan dan Penggunaan E-Wallet Terhadap Tingkat Pendapatan Usaha Dengan E-Commerce Sebagai Variabel Moderasi - Yeskia Martha Sasmita; Saptantinah, Dewi (Jurnal Nirta : Inovasi Multidisiplin, 2025)
. This study aims to analyze the effect of financial literacy and e-wallet usage on business income levels, with e-commerce as a moderating variable in batik fashion MSMEs in Surakarta. A quantitative approach was used with a survey method involving 112 MSMEs selected through purposive sampling. Data were collected using a Likert-scale questionnaire and direct observation and analyzed using multiple linear regression with a t-test at a 0.05 significance level. The results indicate that financial literacy and e-wallet usage have a positive and significant effect on business income, while e-commerce does not moderate this relationship. These findings suggest that MSMEs need to improve financial risk management, digital transaction security, and the optimization of marketing features in e-commerce to enhance revenue. Future research should consider additional variables such as social media or payment gateways and expand the study scope. This study's limitations include respondents' misinterpretation of the questionnaire, time constraints, and difficulties in data collection due to respondents' business activities